Bark: Use, Management and Commerce in Africa - Cunningham, A.B.; Campbell, Bruce M.; Luckert MK (New York Botanical Garden Press, 2014)
ln his introduction, Tony Cunningham invites the reader “to get to know trees – and the landscapes they characterize – through a botany that uses all your senses.” Science offers a succinct description of baobab tree bark, for example, but those who accept Cunningham’s invitation will also observe it “gleaming silvery-gray in the morning sun; the sweet taste of the inner bark (bast), chewed by elephants and thirsty people, or the white edible fruit pulp, tart on the tongue.” More effective conservation and resource management need good science, of course; but the emotional ties forged by direct experience, Cunningham says, are what allow us to augment the ability of science to induce policymakers and the general public to pay attention to what we need to do to keep bark safe.